ETUDE DE L’EXPRESSION DES COMPORTEMENTS MOTIVES DES ELEVES POUR L’EDUCATION PHYSIQUE ET SPORTIVE (EPS) - Lamri, Driss; Hassouni, Taoufik; El Achhab, Youness; El Madhi, Youssef; Nassiri, Abdeljabbar (European Scientific Journal, ESJ, 2014)
The motivation and determination of the many factors that cause the learners desire to learn or not, is a theme that has been widely apprehended in an educational context and sports. This study aims at knowing the various styles of behaviour of the pupils when they are justify for the courses of PES. Hundred and seventy-five pupils stemming from four public secondary establishments of Taza (Morocco), from 12 to 18 years old were subjected to an opened questionnaire evaluating their behavioural expressions according to four times which make a session of physical and sports education PSE : before the course, during the heating, during the course and after the course. The results reveal overall that when the courses of PSE interest the pupils, they express it by classifiable styles of behaviour in the order of: punctuality, the concentration, the active participation and positive emotional demonstrations of physical well-being and good mood after the courses.